Stability of phenolic compounds and antioxidant capacity of concentrated mulberry juice-enriched dried-minced pork slices during preparation and storage. (July 2018) - Cheng, Jing-Rong; Liu, Xue-Ming; Zhang, Wei; Chen, Zhi-Yi; Wang, Xu-Ping
Abstract: Functional foods have been of increasing demand due to the growing consumer awareness of the relationship between diet and health. Addition of healthy ingredients to meat products is an important method for development of functional meat products. In this contribution, functional dried-minced pork slices incorporated with concentrated mulberry juice (CMJ) were developed and stability of phenolic compounds and antioxidant capacity during product preparation and storage were evaluated. The CMJ contained high amounts of total phenolics, anthocyanin and flavonoids (19.13 ± 0.64 mg GAE/g d.m., 4.91 ± 0.18 C3GE mg/g d.m. and 18.39 ± 1.21 mg CE/g d.m., respectively) and showed excellent antioxidant activities in all assays used. CMJ incorporation drastically minimized lipid and protein oxidation of dried-minced pork slices by decreasing thiobarbituric acid-reactive substances (TBARS) value and carbonyls content during processing and storage. Thermal treatment significantly destroyed the main antioxidant ingredients including anthocyanins, flavonoids, and phenolics in dried-minced pork slices with added CMJ; however, this deterioration could be effectively counteracted by using β-cyclodextrin. The redness increased but lightness decreased with CMJ added, and color of the product remained stable during storage. Therefore, CMJ rich in phenolic compounds could be used as a natural antioxidant and pigment in dried-minced pork slices with suitable protective strategy. Highlights: CMJ dramatically minimized lipid and protein oxidation of dried-minced pork slices. CMJ is rich in phenolics and has good antioxidant activity. Antioxidant ingredients added to products were unstable during thermal treatment. β-cyclodextrin exhibited protective effect on phenolic compounds.